Exploring Regulatory Frameworks for Exosome Therapy: Insights and Perspectives - Qiushi Li; Yuxia Li; Jiaqing Shao; Jianhua Sun; Lan Hu; Xia Yun; Chen Liuqing; Likun Gong; Shuxia Wu (Health Care Science)
ABSTRACT Extracellular vesicles (EVs) have emerged as a promising technology for diagnostic and therapeutic applications in clinical settings over the past decade. However, their advancement is hindered by complex technological and regulatory challenges. This review outlines key considerations in the manufacturing process, quality management, and nonclinical evaluation relevant to EV‐based drug development. Furthermore, we summarize and compare technical regulatory requirements across major countries to help clarify the regulatory principles governing EV products. Our analysis reveals an ongoing international debate regarding the regulatory review of EVs. Nevertheless, adopting a risk‐based classification framework that categorizes EV products as advanced therapeutic drugs is a rational approach. Critical challenges include the development of standardized production protocols, a clearer understanding of therapeutic mechanisms, and resolving complex regulatory issues.